Las migraciones procedentes de los países de bajos salarios: desafíos para Europa - Oyarzun, Javier (Papeles del Este, 2007)
This work deals with two aspects of economic immigration in Europe and above all, in Spain. The first is the economic analysis of the effects of immigration from countries with low salaries in the recipient country. The second is a commentary on the regulation of immigration from an economic prism that includes a comparative analysis of the use of a temporary quota and tax on the work of immigrants.